Continuous strength measurements of cement pastes and concretes by the ultrasonic wave reflection method. (10th May 2020) - Lootens, Didier; Schumacher, Marc; Liard, Maxime; Jones, Scott Z.; Bentz, Dale P.; Ricci, Stefano; Meacci, Valentino
Highlights: This paper presents a non-destructive method of estimating mortar compressive strength. This method is based on ultrasonic wave reflection. Measurement are performed over 3 decades of strength. The differences with quasi-static compression tests differ by maximum 20%. Abstract: Concrete compressive strength is a critical design criterion for concrete elements and should, as a consequence, be carefully controlled to ensure structural integrity and intended functionality. As the cementitious binder of concrete hydrates, its strength and elastic modulus increase with time as concrete transitions from a fluid with suspended particles to a rigid but porous solid. Porosity of the material decreases as hydration products fill available space to create a densified structure. Ultrasonic instruments are able to continuously measure the material properties of cementitious materials. This is a significant advantage over destructive, quasi-static compression test of cylinders or cubes at discrete time intervals. Here, we estimate the elastic modulus and compressive strength of a cement paste or concrete from the amplitude of a reflected ultrasonic wave. A series of cement pastes and concretes are tested in quasi-static compression to establish a correlation between compressive strengths estimated from ultrasonic methods and classical compression test. The differences between the compressive strengths obtained by quasi-static compression tests and ultrasonic wave reflection differ by ±20% over a range of compressive strengths spanning more than 3 decades.